Disadvantages of Automated Respiratory Gas Exchange Analyzers - Ramos-Álvarez, Juan José; Lorenzo-Capellá, Irma; Calderón-Montero, Francisco Javier (Frontiers in Physiology, 2020)
The use of automated gas exchange analysis systems in exercise studies is common throughout the industrialized world and are frequently used in sports medicine laboratories for the measurement of maximal oxygen uptake (VO2max), as an integrative parameter that allows the physical condition to be assessed, in spite of its limitations. Actually, the fundamental principles behind the measurement of respiratory gas exchange (RGE) have not changed for a century. It was used a manual Douglas bag method together with separate chemical analyses. The need for faster and more efficient techniques, has conditioned the traditional procedures and determined the emergence of automated systems. However, the validity and reliability of all these different systems is not well known. The common features associates with these systems, also have disadvantages that must be evaluated at the time of the acquisition of an automated equipment: (1) regular quality control checks, which entails other added economic costs, (2) the validity and reliability of the results, which it is necessary to verify, and (3) the user does not know the equations that determine the values of oxygen consumption and carbon dioxide production. This work aims to clarify the disadvantages of these automated systems. At maximum intensities, the variation of VO2max or VO2peak can be very significant in athletes and even more relevant in sick people undergoing a training program. Therefore, considerable care is needed when comparing RGE data with automated systems. New and Noteworthy Actually, stress tests are more conveniently performed with automated systems. It is necessary to examine the validity and reliability of automated respiratory gas exchange systems. The algorithms incorporated in the software, apart from being a “mystery,” show differences with respect to the data provided.